SINGLE-STAGE INVERTER BASED ON MODIFIED BUCK-BOOST CONVERTER - Ramadhani, Naqita
The utilization of renewable energy using a photovoltaic (PV) system that is connected to a utility (grid-connected) can be a solution to the availability of electricity for remote islands in eastern Indonesia. Generally, the inverter used to connect the PV system to the grid is the double-stage inverter. This type of conversion system, which includes the step of increasing the voltage and converting the DC voltage into AC, has drawbacks, namely the large number of components, high losses, and common-mode voltage problems. In this research, a single-stage inverter based on modified buckboost converter is proposed. The proposed single-stage inverter has advantages in the operation of step-up and step-down the input voltage with a wide range of gain, modular and small common-mode voltage ripple as a solution to the problems of the double-stage inverters that are widely used. Testing using a small-scale prototype has been carried out and results are obtained that verify the advantages of the proposed single-stage inverter.